Seed coating with arbuscular mycorrhizal fungi as an ecotechnologicalapproach for sustainable agricultural production of common wheat (Triticum aestivum L.) - Oliveira, Rui S; Rocha, Inês; Ma, Ying; Vosátka, Miroslav; Freitas, Helena (Journal of toxicology and environmental health. Part A, 2016)
The exploitation of arbuscular mycorrhizal (AM) fungi has become of great interest in agriculture due to their potential roles in reducing the need for agrochemicals, while improving plant growth and nutrition. Nevertheless, the application of AM fungi by dispersing inocula in granular form to open agricultural fields is not feasible because nontargeted spreading of inocula over large surface areas results in high cost per plant. Seed coating has the potential to significantly reduce the amount of inoculum needed, resulting in cost reduction and increased efficiency. The aim of this study was to assess whether seed coating with AM fungal inoculum is a feasible delivery system for production of common wheat (Triticum aestivum L.). Wheat seeds were coated with inoculum of Rhizophagus irregularis BEG140 and grown under different fertilization conditions: (1) none, (2) partial, or (3) complete. Data indicated that mycorrhizal inoculation via seed coating significantly increased the dry weight of shoot and seed spikes of wheat associated with reduced fertilization. Assessment of nutritional status of wheat showed that plants inoculated with R. irregularis via seed coating displayed enhanced stem concentrations of potassium (K), sulfur (S), and zinc (Zn). There were no significant differences in root colonization between plants conventionally inoculated with R. irregularis in soil and those inoculated via seed coating. Seed coating with AM fungi may be as effective as conventional soil inoculation and may contribute to reduce the utilization of chemical fertilizers. The application of AM via seed coating is proposed as an ecotechnological approach for sustainable agricultural wheat production.
Keywords: půdní mikrobiologie; mykorhiza; Mycorrhizae; Fertilizers; Triticum; pšenice; Soil Microbiology; Glomeromycota; průmyslová hnojiva; Seeds; zemědělství; Agriculture; semena rostlinná